Design e paisagem urbana – estratégias de design para parques de Goiânia - Silva, Matheus Lima da (2018)
This research approaches Goiânia’s parks as part of the contemporary urban landscape and as an architectural element of citizenship production. It investigates the nature of these environments through the design optics. It was observed that even being a public space, the urban parks present aggregations and segregations in its uses. In response to this, it is possible to notice that some of this behaviors are detracted, generating interactions and conflicts in the functioning of these environments. Apparently, the current physical distribution of the environment has contributed to this behavior. The hypothesis is that through design strategies, people's interaction can be effectively triggered for the production of citizenship. By this perspective, the aim was to understand the functioning of contemporary urban parks and to identify how the space interfere in social behavior, in order to recover their primary function, which is the use of the environment in a collectively way, but with belonging. The methodology is based on a historical and qualitative approach, through the analysis of parks that present similar morphological structures. The expectation is that these design strategies can direct their 're-operation' in favor of interaction among users.